NSC828779 Alleviates Renal Tubulointerstitial Lesions Involving Interleukin-36 Signaling in Mice - Shin-Ruen Yang (MDPI AG, 2021)
Renal tubulointerstitial lesions (TILs), a common pathologic hallmark of chronic kidney disease that evolves to end-stage renal disease, is characterized by progressive inflammation and pronounced fibrosis of the kidney. However, current therapeutic approaches to treat these lesions remain largely ineffectual. Previously, we demonstrated that elevated IL-36α levels in human renal tissue and urine are implicated in impaired renal function, and IL-36 signaling enhances activation of NLRP3 inflammasome in a mouse model of TILs. Recently, we synthesized NSC828779, a salicylanilide derivative (protected by U.S. patents with US 8975255 B2 and US 9162993 B2), which inhibits activation of NF-κB signaling with high immunomodulatory potency and low IC50, and we hypothesized that it would be a potential drug candidate for renal TILs. The current study validated the therapeutic effects of NSC828779 on TILs using a mouse model of unilateral ureteral obstruction (UUO) and relevant cell models, including renal tubular epithelial cells under mechanically induced constant pressure. Treatment with NSC828779 improved renal lesions, as demonstrated by dramatically reduced severity of renal inflammation and fibrosis and decreased urinary cytokine levels in UUO mice. This small molecule specifically inhibits the IL-36α/NLRP3 inflammasome pathway. Based on these results, the beneficial outcome represents synergistic suppression of both the IL-36α-activated MAPK/NLRP3 inflammasome and STAT3- and Smad2/3-dependent fibrogenic signaling. NSC828779 appears justified as a new drug candidate to treat renal progressive inflammation and fibrosis.